THE WRITER'S WORLD VIEW AND ARTISTIC IDEA - Toraeva Dilnoza Nematullaevna (International Journal of Innovations in Engineering Research and Technology, 2022)
The article reveals that the process of artistic creation, the emergence of a literary work as a creative intention, and the characteristics of artistic interpretation are directly related to the personality of the creator as a special literary phenomenon as one of the leading features of Uzbek literary studies in the period of independence. It has been proven that the author's ideological-emotional attitude to the events described in the work of art, the choice of the system of images and the poetic perception of the problem through them, as well as the artistic judgment, are the basis of the writer's creative laboratory. The importance of the creative process based on the artist's aesthetic ideal, worldview, cultural-educational level, life experience, skills, talent and capacity is based on the development of a work of art. In researching the issue of artistic idea, creative imagination and aesthetic interpretation, the writer's creative self, the structure of his thoughts, the pair of writer and artistic work, the poetic world and spiritual world of the creator were studied in the context of the whole literary process. The consistent improvement of the development of literary and aesthetic views in world literature is the basis for the emergence of scientific concepts related to the gradual development of artistic thinking. Therefore, the study of the uniqueness of the artistic world, a critical approach to it is bound to benefit the development of the literature of every nation. Therefore, it is important to scientifically examine the process of literary creativity, to study the factors related to the birth and materialization of creative intention, to show the peculiarities of artistic-aesthetic interpretation, and to theoretically justify the problems related to the manifestation of the creative personality